Role Of Zinc Supplementation in Growth and Neuro-Development of Premature and Small for Gestational Age (SGA) Babies - Manish Parakh; BD Gupta; Suman Bhansali; Poonam Parakh; Pramod Sharma; Manisha Gurjar; Narendra Chhangani (National Journal of Community Medicine, 2012)
Objectives: A negative Zinc balance exists in preterm and small for gestational age infants. The current study evaluates the role of zinc supplementation on growth and neurodevelopmental outcome of these infants.